2020
DOI: 10.1016/j.jsat.2020.108061
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine misuse in adults with alcohol use disorder: Prevalence, motives and patterns of use

Abstract: Objective.-Benzodiazepines are among the most commonly misused drugs. Despite the known risks of combining benzodiazepines and alcohol, little is known about misuse among people with alcohol use disorder (AUD). Our aim was to characterize the prevalence, correlates, and patterns of misuse of benzodiazepines in adults with AUD.Method.-Adults receiving treatment for AUD (N=258) completed a battery of questionnaires. We used descriptive statistics to characterize the prevalence and patterns of misuse and we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 25 publications
2
8
0
Order By: Relevance
“…Moreover, AUD severity was higher in patients with BZD consumption. In multivariate analysis, we found that age, psychiatric comorbidities and lifetime use of cocaine were significantly associated with BZD misuse, as reported in other studies [5,15]. BZD misuse in patients with AUD has major impacts on public health because these SUD are directly and indirectly linked to higher mortality [1,16].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Moreover, AUD severity was higher in patients with BZD consumption. In multivariate analysis, we found that age, psychiatric comorbidities and lifetime use of cocaine were significantly associated with BZD misuse, as reported in other studies [5,15]. BZD misuse in patients with AUD has major impacts on public health because these SUD are directly and indirectly linked to higher mortality [1,16].…”
Section: Discussionsupporting
confidence: 78%
“…In our population, AUD was severe in 91% of BZD users and this may explain the high rate of BZD misuse. In addition, in our population, the concomitant consumption of illicit psychoactive substances was high (25% of patients consumed cocaine in the last month before hospitalization), but in line with previous studies [5,15]. Nevertheless, due to the AUD severity that required hospitalization for alcohol withdrawal, our population is not comparable with the general population of patients with AUD.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Here, emergent theories of causation suggest use as a ‘coping strategy’ to manage anxiety, or as an alternative given lack of access to preferred drugs of choice. Shifts to increased benzodiazepine use is an obvious concern given the potential for harm, including through dependence, polysubstance use ( McHugh et al, 2020 , Votaw et al, 2020 ), and increased risk of drug-related morbidity and mortality (particularly among people who are opioid dependent) ( Dasgupta et al, 2016 , Macleod et al, 2019 , McCowan et al, 2009 , Park et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%